GENEFLOW - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Published by the International Board for Plant Genetic Resources (IBPGR), this is a biannual revue in full colour. It aims to keep readers informed of the state of research on plant genetic resources by means of short articles on research projects,...